2019
DOI: 10.1007/s10722-019-00828-z
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of a new weed in maize plantations: characterization and genetic structure using microsatellite markers

Abstract: The objective of this work was to assess the genetic variability and structure of a new weed in Spanish maize fields, and investigate its geographical patterns using 17 microsatellites. Commercial maize varieties (C), maize-like weeds (MLW), putative hybrids with C (WCH), and teosintes (Tm: Zea mays ssp. mexicana and Tp: Z. mays ssp. parviglumis) were analyzed. The weed genetic diversity (MLW and WCH: 0.52) was the lowest (C: 0.59, Tm: 0.66, and Tp: 0.71). Weeds (0.21) and teosintes (Tm: 0.27, Tp: 0.34) showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 37 publications
0
11
0
3
Order By: Relevance
“…Instead, Spanish teosintes were found intermediate between maize and mexicana (25). Microsatellite markers further confirmed the importance of maize contribution to the genetic make-up of Spanish teosintes (26). Here, we collected French teosinte populations and describe for the first time their genetic diversity.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Instead, Spanish teosintes were found intermediate between maize and mexicana (25). Microsatellite markers further confirmed the importance of maize contribution to the genetic make-up of Spanish teosintes (26). Here, we collected French teosinte populations and describe for the first time their genetic diversity.…”
Section: Introductionmentioning
confidence: 63%
“…In other words, our results are consistent with a scenario where European maize varieties adapted to temperate latitudes have contributed to the establishment of teosintes in Europe. Note that hybridization is seemingly still occurring, as plants carrying hybrid-like cobs are regularly observed in infested maize fields in Spain (25,26) as well as in France (SI Appendix, Fig. S10).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Vega‐Alvarez et al (2017) found F IS = 0.318 for Z. mays subsp. parviglumis , while Díaz et al (2020) and Rocandio‐Rodríguez et al (2014), respectively, reported F IS values of 0.33 and 0.314 for Z. mays subsp. parviglumis and 0.28 and 0.381 for Z. mays subsp.…”
Section: Discussionmentioning
confidence: 98%
“…mexicana . Díaz et al ( 2020 ) found that ES teosinte has a complex origin being related to both commercial maize and wild teosinte ( Z. mays subsp. mexicana and Z. mays subsp.…”
Section: Introductionmentioning
confidence: 99%